Redesign of Anaerobic-Aerobic Biofilter for Domestic Wastewater Treatment Plant In Textile Industry - Rachmanu Eko Handriyono; Amelia Kencana Rukmi (Journal of Civil Engineering, Planning and Design, 2022)
One of the textile industries in Pasuruan already has a Domestic Wastewater Treatment Plant (WWTP) with a capacity of 35 m3 /day. The treatment process combined physical, chemical, and biological processes using an anaerobic-aerobic biofilter. The domestic WWTP consists of a collection tank, equalization tank, anaerobic-aerobic biofilter tank, a filtration tank, and a chlorination tank. Existing conditions indicate that the domestic wastewater generated exceeds the capacity of the WWTP. Additional employees become one of the factors causing the increase in domestic wastewater discharge. Inadequate capacity has forced the company to bypass domestic waste into rivers. This biofilter was chosen because it could reduce high BOD values, have low operating costs, and operate efficiently. The anaerobic-aerobic biofilter reactor consists of a pre-settling tank, anaerobic tank, aerobic tank, and final settling tank. The evaluation results denoted that detention time in pre-settling, anaerobic, and settling units did not meet the design criteria. Thus, changing the design according to the design criteria. The redesign result of the anaerobic biofilter includes the pre-settling tank with a diameter of 2,5 m and a length of 3 m, an anaerobic tank with a diameter of 2,5 m and a length of 15 m, so that the total volume in the anaerobic reactor is 88.3 m3 . Then anaerobic bath with a diameter of 2,5 m and a length of 6 m and a final settling tank with a diameter of 2,5 m and a length of 1,5 m so that the total volume in the aerobic biofilter reactor is 36,7 m3 .